Magnetic Reconnection in a Compact Magnetic Dome: Chromospheric Emissions and High-velocity Plasma Flows - J. M. da Silva Santos; E. Dunnington; R. Jarolim; S. Danilovic; S. Criscuoli (The Astrophysical Journal)
Magnetic reconnection at small spatial scales is a fundamental driver of energy release and plasma dynamics in the lower solar atmosphere. We present observations of a brightening in an active region, captured in high-resolution data from the Daniel K. Inouye Solar Telescope using the Visible Broadband Imager and the Visible Spectro-Polarimeter (ViSP). The event exhibits Ellerman bomb−like morphology in the H β filter, associated with flux cancellation between a small negative-polarity patch and an opposite polarity plage. Additionally, it displays enhanced emissions in Ca ii K, hot elongated features containing Alfvénic plasma flows, and cooler blueshifted structures. We employ multiline, nonlocal thermodynamic equilibrium inversions of the spectropolarimetric data to infer the stratification of the physical parameters of the atmosphere. Furthermore, we use the photospheric vector magnetogram inferred from the ViSP spectra as a boundary condition for nonlinear force-free field extrapolations, revealing the three-dimensional distribution of squashing factors. We find significant enhancements in temperature, velocity, and microturbulence confined to the upper photosphere and low chromosphere. Our findings provide observational evidence of low-altitude magnetic reconnection along quasi-separatrix layers in a compact fan-spine-type configuration, highlighting the complex interplay between magnetic topology, energy release, and plasma flows.